Effects of Ramadan fasting on the diurnal variations of physical and cognitive performances at rest and after exercise in professional football players - Khemila, Syrine; Romdhani, Mohamed; Farjallah, Mohamed Amine; Abid, Rihab; Bentouati, Emna; Souissi, Mohamed Abdelkader; Abedelmalek, Salma; Garbarino, Sergio; Souissi, Nizar (Frontiers in Psychology, 2023)
This study assessed the effects of Ramadan fasting (RF) on the diurnal variation of physical and cognitive performances at rest and after exercise. In a randomized order, 11 male football players (age: 19.27±0.9; height: 1.79±0.04cm; body mass: 58±6.90kg; BMI: 42±2.11kg/m2) completed a 30-s Wingate test [i.e., mean (MP) and peak powers (PP)] at 07:00h, 17:00h and 21:00h on five occasions: one week before Ramadan (BR); the second (R2); the third (R3); the fourth (R4) week of Ramadan; and two weeks after Ramadan (AR), with an in-between recovery period of ≥72h. Simple (SRT) and choice (CRT) reaction times, mental rotation test (MRT) and selective attention (SA) test were measured before and after Wingate test. Compared to BR, RF decreased MP at 17:00h (p<0.05, d=1.18; p<0.001, d=2.21, respectively) and PP at 17:00h (p<0.05, d=1.14; p<0.001, d=1.77, respectively) and 21:00h (p<0.01, d=1.30; p<0.001, d=2.05, respectively) at R3 and R4. SRT (p<0.001,d=1.15; d=1.32, respectively), number of correct answers (MRTE) (p<0.05, d=1.27; d=1.38, respectively) and SA (p<0.01, d=1.32; d=1.64, respectively) increased during R2 and R3 in the evening before exercise compared to BR. Short term maximal exercise enhanced SRT (p<0.01, d=1.15; p<0.001, d=1.35, respectively), MRTE (p<0.001, d=2.01; d=2.75 respectively) and SA (p<0.05, d=0.68; d=1.18, respectively) during R2 and R3 in the evening. In comparison to BR, sleep latency and sleep duration increased during R3 (p<0.001, d=1.29; d=1.74, respectively) and R4 (p<0.001, d=1.78; d=2.19, respectively) and sleep quality increased in R2, R3 and R4 (p<0.01, d=1.60; p<0.001, d=1.93; d=2.03, respectively). During RF, anaerobic and cognitive performances were unaffected in the morning but were impaired in the afternoon and evening. Short-term maximal exercise mitigates the negative effects of fasting on cognitive performance. Maximal exercise could thus partially counteract the effect of fasting on cognitive function.